Effect of increased physical activity on physical fitness in an overweight and/or obese group of adolescents - Ruiz López, IM.; Martín-Matillas, M.; Delgado-Fernández, M.; Delgado-Rico, E.; Campoy Folgoso, C.; Verdejo-García, A. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2021)
This study evaluated the effect of increased physical activity (PA) to achieve PA recommendations according to the World Health Organization for improving health in a group of 42 adolescents (28 girls) with overweight / obesity (BMI = 29.37 ± 4.5 Kg / m²). The 12 weeks treatment consisted in the prescription and follow-up of the PA guidelines divided in two phases: intensive (weekly follow-up) and extensive (fortnightly follow-up). PA level was assessed using the Physician-based Assessment and Counseling questionnaire and the Physical Fitness using upper body isometric strength test, lower body explosive strength test and cardiorespiratory fitness test, all from the ALPHA battery fitness tests. After treatment, a significant improvement was observed (p <0.05) in cardiorespiratory fitness. In conclusion, this study shows that increasing PA practice and meeting the weekly recommendations of 300 minutes of moderate-vigorous PA, the adolescents’ group improved their cardiorespiratory fitness.